Intention to visit a world-famous tourism village in Bali: The role of destination image, self-congruence, and destination personality - Usep Suhud; Najihah Hanisah Marmaya; Suddin Lada; Umi Wahidah (Atlantis Press, 2023)
This study examined the effect of destination image, self-congruence, and destination personality on visit intention, with the case of Panglipuran village in Bali, a village which possesses national and international achievements. Data was collected in Bali and Surabaya. The participants were selected using the convenient sampling method. Data were analyzed utilizing exploratory factor analysis and structural equation models. As a result, destination image owns a significant effect on self-congruence and destination personality. Furthermore, congruence and destination personality produce a significant effect on visit intention. These findings deepen the study of village tourism destinations.